Coping Across the Transition to Adolescence: Evidence of Interindividual Consistency and Mean-Level Change. (October 2015) - Valiente, Carlos; Eisenberg, Nancy; Fabes, Richard A.; Spinrad, Tracy L.; Sulik, Michael J.
The goal of this study was to examine various forms of coping across the transition to adolescence, with a focus on interindividual (correlational) consistency of coping and mean-level changes in coping. Adolescents' emotional coping, problem solving, positive cognitive restructuring, avoidance, and support seeking in response to everyday stressors were assessed via a daily diary beginning when participants ( N = 155) were approximately 9 years old and continued every 2 years for a total of four assessments. Most indices of coping demonstrated some interindividual consistency across time. Emotional coping and support-seeking coping declined over time, whereas positive cognitive restructuring and avoidance increased as adolescents aged. The discussion focuses on the implications of the findings and suggestions for advancing this line of inquiry.